2018
DOI: 10.3390/foods7090133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dual Modification with Succinylation and Annealing on Physicochemical, Thermal and Morphological Properties of Corn Starch

Abstract: The objective of this study was to investigate the effects of annealing, succinylation, and a dual modification process (succinylation–annealing) on the physicochemical, thermal, and morphological properties of corn starch. Specifically, the properties of interest were the water-binding capacity (WBC), swelling power, paste clarity, solubility, pasting properties, stability ratio, and thermal and morphological characteristics. The dual modification process increased the physicochemical properties (WBC, swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The swelling index generally decreased with modification and annealed starch had the lowest values. The results are in line with other studies, which showed that annealing reduces swelling, while succinylation increases solubility (Ariyantoro et al, 2018). The swellability of starches is of great significance in tablet formulations because the disintegrant properties of starches have been shown to be affected by swelling and wicking action (Musa et al, 2008).…”
Section: Physicochemical and Functional Properties Of The Starchessupporting
confidence: 91%
See 3 more Smart Citations
“…The swelling index generally decreased with modification and annealed starch had the lowest values. The results are in line with other studies, which showed that annealing reduces swelling, while succinylation increases solubility (Ariyantoro et al, 2018). The swellability of starches is of great significance in tablet formulations because the disintegrant properties of starches have been shown to be affected by swelling and wicking action (Musa et al, 2008).…”
Section: Physicochemical and Functional Properties Of The Starchessupporting
confidence: 91%
“…This suggests that the incorporation of the disintegrants intra-granularly led to increased intermolecular forces between the particles as a result of either aspartic melting on production of heat during 2016 ;No, Mun, Shin, 2019) while the peak at 1713.99 cm -1 was attributable to the stretching vibration of C=O indicating existing ester carbonyl groups. Annealing modifies starch without damaging the granules, thus the spectra for the annealed lima bean starch was similar to that of the native starch (Ariyantoro et al, 2018).…”
Section: Crushing Strengthmentioning
confidence: 80%
See 2 more Smart Citations
“…Lysine succinylation is an evolutionarily conserved posttranslational modification (PTM) known to be involved in the regulation of diverse cellular process [1,2,3,4,5,6,7]. The succinylation process modifies a target protein with a succinyl group (–CO–CH 2 –CH 2 –CO 2 H), which is transmitted from succinyl-CoA to the specific α-amino group of a lysine residue [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%